Henry Rider Haggard’s Nordicism? When Black Vikings fight alongside White Zulus in South Africa - Gilles TEULIÉ (E-REA)
This article surveys the question of racism and racial representations in the works of Henry Rider Haggard. Among the numerous articles and chapters written on that topic, few have tackled the issue from the perspective of the nordicist ideology that developed in the late 19th century and the early years of the 20th. This idea that Northern European people were part of an “elite race” was promoted, particularly in Britain where saxonism was brushed aside as it excluded the “Celtic fringe” of the British Isles. Yet, Late Victorian ideologists were adamant to advertise a consensual Empire which would unite all “British” peoples. The Viking (Middle) Age was thus promoted as a common heroic background to both the Saxons and Celts as the “Sea Kings” plundered the shores of the British Isles and even settled there. Haggard evokes the Vikings but also the Norse elite warriors, the Berserkir in some of his novels. This article purports to examine Haggard’s engagement with the ambient racial ideologies of the period: was he just a man of his time or did he have another vision for race relations in South Africa?